STRATEGI PENINGKATAN NILAI TUKAR NELAYAN TRADISIONAL DI KABUPATEN SAMBAS - Aditya Nugraha; Bambang Kurniadi; Nia Permatasari (Pusat Riset Perikanan, 2021)
The Indonesian government has committed to supporting the Sustainable Development Goals. One indicator is poverty reduction. In 2020, the agricultural sector was the primary source of income for 46.3% of poor households in Indonesia, and the 16.2 million fishermen are below the poverty line. West Kalimantan Province is the province with the highest number of fishers on the island of Kalimantan. The welfare of fishers does not follow the significant fishery potential in West Kalimantan Province. Sambas Regency is the second Regency in West Kalimantan Province which has the most considerable number of capture fisheries production and the most significant number of fishers. The fisherman's exchange rate concept compares the value of fisherman's output against the goods and services needed for fishing business purposes and the consumption fisherman households. One way to provide optimal benefits to capture fisheries business is to manage risk. The purpose of this study is to identify the welfare of traditional fishing fishers based on the fisherman's exchange rate and the risks that affect the fishermen's capture fisheries business and formulate strategies to increase the fisherman's exchange rate. The research was design using qualitative and quantitative approaches. As many as 54% of respondents have a fisherman's exchange rate of 0 1. Risks with a high category are damage to fishing gear, unpredictable weather, and the length of time it takes to recede in the fishing area. The risk in the medium type is the low selling price and the decrease in the number of fish resources. Risk can be control by increasing the ability to capture fisheries business management, increasing the use of information technology in the fishing business, and increasing the accessibility of capital for fishers facilitated by the government.Pemerintah Indonesia telah berkomitmen untuk mendukung Sustainable Development Goal’s. Salah satu indikatornya adalah penurunan angka kemiskinan. Pada tahun 2020, sektor pertanian merupakan sumber penghasilan utama dari 46,3% rumah tangga miskin di Indonesia dan 16,2 juta nelayan berada di bawah garis kemiskinan. Provinsi Kalimantan Barat merupakan provinsi dengan jumlah nelayan terbanyak di Pulau Kalimantan. Besarnya potensi perikanan di Provinsi Kalimantan Barat tidak diikuti oleh kesejahteraan dari Nelayan. Kabupaten Sambas merupakan Kabupaten kedua di Provinsi Kalimantan Barat yang memiliki jumlah produksi perikanan tangkap terbesar dan jumlah nelayan terbanyak. Konsep nilai tukar nelayan adalah membandingkan nilai produksi nelayan terhadap barang dan jasa yang diperlukan untuk usaha penangkapan dan konsumsi rumah tangga nelayan. Salah satu cara untuk memberikan keuntungan optimal pada usaha perikanan tangkap adalah dengan mengelola risiko. Tujuan dari penelitian ini adalah mengidentifikasi kesejahteraan nelayan tangkap tradisional berdasarkan nilai tukar nelayan, serta risiko yang berpengaruh terhadap usaha perikanan tangkap nelayan dan merumuskan strategi guna meningkatkan nilai tukar nelayan. Penelitian didesain dengan menggunakan pendekatan kualitatif dan kuantitatif. Sebanyak 54% responden memiliki nilai tukar nelayan sebesar 0 ≤ 1. Risiko dengan kategori tinggi adalah kerusakan alat tangkap, cuaca sulit diprediksi, serta lamanya waktu surut di area penangkapan. Risiko dengan kategori sedang adalah rendahnya harga jual dan penurunan jumlah sumberdaya ikan. Pengendalian risiko dapat dilakukan dengan cara meningkatkan kemampuan manajemen usaha perikanan tangkap, meningkatkan penggunaan teknologi dalam usaha tangkap dan peningkatan aksesibilitas permodalan bagi nelayan yang difasilitasi oleh pemerintah